ANALISIS KETERAMPILAN GEOMETRI SISWA DALAM MEMECAHKAN MASALAH GEOMETRI BERDASARKAN TINGKAT BERPIKIR VAN HIELE - Muhassanah, Nuraini; Sujadi, Imam; Riyadi, Riyadi (Jurnal Pembelajaran Matematika, 2014)
Abstract:The objective of this research was to describe the VIII grade students geometry skills atSMP N 16 Surakarta in the level 0 (visualization), level 1 (analysis), and level 2 (informaldeduction) van Hiele level of thinking in solving the geometry problem. This research was aqualitative research in the form of case study analyzing deeply the students geometry skill insolving the geometry problem based on van Hiele level of thingking. The subject of this researchwas nine students of VIII grade at SMP N 16 Surakarta consisted of three students of level 0(visualization), three students of level 1 (analysis), and three students of level 2 (informaldeduction) obtained from clustering technic. The data in this research was the characteristics ofgeometry skills obtained from the recording script of the interview done twice for the sake oftriangulation. The result of this research was the geometry skills of students in solving thegeometry problem. Students of level 0 (visualization) at the visual skill can define the square basedon the shape appearance; descriptive skill, can group the right name of the pictures given; drawingskill, can draw the square by labeling the certain parts; logical skill, can understand theconservation of the square picture in any position and realize the similarity from some pictures ofsquare; and application skill, can correlate the given information (physical object) and develop itinto geometry model as well as explain the characteristics of geometry from the physicalappearance. Then, the syudents of level 1 (analysis) at the visual skill, can explain thecharacteristics of the picture; descriptive skill, can define the square based on the characteristics;drawing skill, can construct the picture based on the given characteristics (verbal information) anddraw draw the other square; logical skill can mention the differences of squares and realize that thecharacteristics of square can be used to differentiate kinds of square; and application skill, can usethe geometry model in solving the problem. Next, the students of level 2 (informal deduction) atvisual skill, can admit the relation from any kinds of square by admitting the general characteristic;descriptive skill, can create the sentences showing the relation among the square based on thegeneral characteristics; drawing skill, can draw other square from the given square and explain thecharacteristics; logical skill, can use the characteristics of a square to decide a class of squarewhich is in the other kinds of square; and application skill, can use the model concept ofmathematic representing the relation among the objects.Key words: geometry kill, van Hiele level of thinking, problem solving, and geometry.